2016
DOI: 10.4191/kcers.2016.53.3.354
|View full text |Cite
|
Sign up to set email alerts
|

Carbonation Behavior of Lightweight Foamed Concrete Using Coal Fly Ash

Abstract: The purpose of this study was to prepare lightweight foamed concrete by mixing coal fly ash of circulating fluidized bed combustion(CFBC) with cement, and to develop uses for recycling by analyzing carbonation behavior resulting from a change in conditions for pressurized carbonation. For concrete, CFBC coal fly ash was mixed with Portland cement to the water-binder ratio of 0.5, and aging was applied at room temperature after 3 days of curing at 20 o C, RH 60%. For carbonation, temperature was fixed at 60 o C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Xia et al [126] utilized FBCFA in non-autoclaved aerated concrete and their study showed that FBCFA can be used as raw materials in NAAC production at a proportion of around 65%. Lee and Lee [127] studied lightweight foamed concrete prepared from FBCFA, which a high free CaO amount was stabilized using carbonation. They replaced cement 30 wt % and stored more than 90% of the CO 2 .…”
Section: Aerated Concretementioning
confidence: 99%
“…Xia et al [126] utilized FBCFA in non-autoclaved aerated concrete and their study showed that FBCFA can be used as raw materials in NAAC production at a proportion of around 65%. Lee and Lee [127] studied lightweight foamed concrete prepared from FBCFA, which a high free CaO amount was stabilized using carbonation. They replaced cement 30 wt % and stored more than 90% of the CO 2 .…”
Section: Aerated Concretementioning
confidence: 99%